Venous Thromboembolism among Noncritically Ill Hospitalized Children: Key Considerations for the Pediatric Hospital Medicine Specialist - Morrison, John M.; Betensky, Marisol; Kiskaddon, Amy L.; Goldenberg, Neil A. (Seminars in Thrombosis and Hemostasis, 2021)
Venous thromboembolism (VTE) is a leading cause of morbidity and preventable harm among noncritically ill hospitalized children. Several clinical factors relevant to the noncritically ill hospitalized child significantly increase the risk of VTE including the presence of central venous catheters, systemic inflammation, and prolonged immobilization. Although risk mitigation strategies have been described, the diagnosis, treatment, and prevention of VTE require standardization of institutional practices combined with multidisciplinary collaboration among pediatric hospitalists, hematologists, and other care providers. In this narrative review, we summarize the epidemiology of VTE, risk models identifying high-risk conditions associated with VTE, and prevention and treatment strategies. We further describe successful quality improvement efforts implementing institutional VTE risk stratification and thromboprophylaxis procedures. Finally, we highlight unique challenges facing pediatric hospital medicine specialists in the era of the COVID-19 pandemic, including caring for adults admitted to pediatric hospital units, and describe future research opportunities for VTE in the noncritically ill hospitalized child.
Keywords: thromboembolism; deep vein thrombosis; thromboprophylaxis; pediatric hospital medicine